2008
DOI: 10.1063/1.2919805
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of solid particles in a tangle of superfluid vortices at low temperatures

Abstract: We present results of numerical study of motion of micron-size, neutrally buoyant, solid particles in liquid helium at temperatures small enough that the normal fluid is negligible and turbulence manifests itself as a tangle of superfluid line vortices. Based on dynamically self-consistent model of interaction between a solid particle and the quantized vortex, we analyze first an influence of temperature on particle trapping on the vortex core. We find that the particle can be trapped only in the case where th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Due to inertia, however, the initial particle's backward motion will develop along evolution time scales which are much larger than the ones for the vortex dipole, which, then decouples from the particle. Its worth emphasizing that an analogous connection between small viscous dissipation and the suppression of particle trapping in quantum vortices has been previously noticed from three-dimensional numerical simulations of particle dynamics in vortex tangles [30].…”
Section: Flow Regimessupporting
confidence: 56%
See 2 more Smart Citations
“…Due to inertia, however, the initial particle's backward motion will develop along evolution time scales which are much larger than the ones for the vortex dipole, which, then decouples from the particle. Its worth emphasizing that an analogous connection between small viscous dissipation and the suppression of particle trapping in quantum vortices has been previously noticed from three-dimensional numerical simulations of particle dynamics in vortex tangles [30].…”
Section: Flow Regimessupporting
confidence: 56%
“…Our analysis is inspired by superfluid counterflow regimes similar to the ones investigated in experiments [27,28,33] and numerical simulations [30,31]. We mean approximately equal mass densities ρ n and ρ s for the normal and superfluid components of the condensate, respectively, a condition realized at temperatures close to 2 K, and spherical tracking particles with radii around 2.5 µm.…”
Section: Phenomenological Ingredientsmentioning
confidence: 98%
See 1 more Smart Citation
“…That the combination of the above reconnection model with the particular α and β values work as expected in practice was shown in Ref. 24. Indeed, in this work, in order to keep a constant tangle length during a T = 0 K computation, thus, to compensate for reconnection induced losses, an energy injection into the system in the form of superfluid vortex rings had to be applied.…”
Section: B Vortex Reconnectionsmentioning
confidence: 99%
“…Since GrossPitaevskii fluid dynamics studies have shown that reconnections transform some of the kinetic flow energy into acoustic energy (Parker et al 2004), one expects that Schwarz surgery would, in effect, be a dissipative process at large incompressible scales. For the particular surgery employed here, this was shown to be the case, since Kivotides, Sergeev & Barenghi (2008b) had to force the superfluid vortex tangle in order to achieve a state with statistically constant length, L, at temperature T = 0 K. Overall, Schwarz surgery is a heuristic model of refined microscopic physics. The same holds for its application in the formulation of the vortex tube model of classical incompressible turbulence, where it models subgrid viscous reconnection physics (Kivotides & Leonard 2003).…”
Section: Superfluid Dynamicsmentioning
confidence: 99%